Biological and Molecular Factors Predicting Response to Adoptive Cell Therapies in Cancer. (19th April 2022) - Ferrer, Gerardo; Álvarez-Errico, Damiana; Esteller, Manel
Abstract: Adoptive cell therapy (ACT) constitutes a major breakthrough in cancer management that has expanded in the past years due to impressive results showing durable and even curative responses for some patients with hematological malignancies. ACT leverages antigen specificity and cytotoxic mechanisms of the immune system, particularly relying on the patient's T lymphocytes to target and eliminate malignant cells. This personalized therapeutic approach exemplifies the success of the joint effort of basic, translational, and clinical researchers that has turned the patient's immune system into a great ally in the search for a cancer cure. ACTs are constantly improving to reach a maximum beneficial clinical response. Despite being very promising therapeutic options for certain types of cancers, mainly melanoma and hematological malignancies, these individualized treatments still present several shortcomings, including elevated costs, technical challenges, management of adverse side effects, and a limited population of responder patients. Thus, it is crucial to discover and develop reliable and robust biomarkers to specifically and sensitively pinpoint the patients that will benefit the most from ACT as well as those at higher risk of developing potentially serious toxicities. Although unique readouts of infused cell therapy success have not yet been identified, certain characteristics from the adoptive cells, the tumor, and/or the tumor microenvironment have been recognized to predict patients' outcome on ACT. Here, we comment on the importance of biomarkers to predict ACT chances of success to maximize efficacy of treatments and increase patients' survival.